Towards a sediment reference material database for the Danube River - Seremet, Radu; Andreicovici, Iulian; Ise, Silvia; Ujeniuc, Sorin; Pojar, Iulian; Suvaila, Rares (HNPS Advances in Nuclear Physics, 2025)
The second largest river in Europe, which has the richest biodiversity within its delta, does not have a sediment reference material database yet. Although there is a plethora of data available, spanning decades and large areas of interest, there is no common ground for data interpretation. The purpose of the database we are starting is to compile the already existing results and our own output from various sources on one hand, and to provide a standardized framework in terms of methodology and uncertainty budget evaluation. This paper briefly presents the procedure proposed for sample treatment and analysis, and focuses on the radionuclide map generated for data visualization. Among the software solutions available, we chose the ones capable of providing clear results for the data integration process in order to obtain a simple, still powerful tool for radionuclide concentration assay, including dynamics. The results are promising and adapted to this need for the Danube River, opening the way to generating a fully documented map for all the natural and anthropogenic radionuclides of interest. The purpose of the present work is not only to track the evolution of nuclide concentration, but also to become able to make predictions.